Генерация импульса Эйри точечным источником - Золотарев, Д. А. (ХНУРЕ, 2012)
An Airy pulse in time domain is derived for the first time using Green’s function for the paraxial equation. The pulse is generated by a source located at some point. Temporal dependence of this source is given by the Airy function that conditioned excitation the Airy pulse. This pulse is decelerating and its velocity trends to zero at infinite distance from the source.
Keywords: импульс Эйри; точечный источник; излучение; функция Грина; ток